Drought, water management, and social equity: Analyzing Cape Town, South Africa's water crisis - Calverley, Cameron M.; Walther, Suzanne C. (Frontiers in Water, 2022)
Climate change impacts on hydrologic systems, coupled with increasing water demand and a growing global population, has led to depleted water resources in semi-arid regions around the world. This increase in water shortages has significant implications for environmental justice and equity concerns. One such region impacted by both water scarcity and deep-seated inequality is the Western Cape of South Africa, whose drought crisis reached peak recognition when the City of Cape Town released its notice of ‘Day Zero’ in 2018. This study examines the changes in physical factors prior to and during the 2015-2018 drought in Cape Town and evaluates how policy decisions made in response to this event interacted with existing social injustices. Analysis of the physical data finds only a slight direct relationship between rainfall and dam levels (r2 = 0.3), suggesting a more complex narrative for the decrease in water supply, including increased water use and management decisions. Of the many policies implemented to avoid Day Zero, some were found to be more effective and can be utilized long term. The study also finds that the Cape Town water crisis has unveiled and heightened existing inequalities through placing a disproportionate financial burden on low-income communities. As droughts become more common, Cape Town provides a crucial case study for understanding the social, political, and environmental implications of drought management in the future.